Method for manufacturing positive electrode and solid electrolyte composite structure for lithium ion battery

By depositing positive electrodes and solid electrolytes on the substrate and heat treatment to form a composite structure, the problem of insufficient uniformity of lithium dendrites and solid electrolytes in the prior art is solved, and a cyclic lithium-ion battery pack with efficient charging and long life is achieved.

CN119852543APending Publication Date: 2025-04-18GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411444571.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-17
Filing Date
2024-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing battery packs with circulating lithium ions are prone to form lithium dendrites under high efficiency charging and high current density, and the uniformity of the solid electrolyte and interface contact ability are insufficient, which affects the cycle life of the battery pack.

Method used

By depositing the positive electrode and the solid electrolyte on the substrate, a composite structure is formed, and the solid electrolyte layer is sintered by heat treatment to ensure good interface contact and uniform distribution with the positive electrode.

Benefits of technology

The uniformity of solid electrolytes and high current density are achieved, the formation of lithium dendrites is reduced, and the cycle life and charging rate of the battery pack are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852543A_ABST
    Figure CN119852543A_ABST
Patent Text Reader

Abstract

A method of manufacturing a composite structure for a battery for cycling lithium ions includes: depositing a positive electrode precursor on a substrate to form a positive electrode layer; compacting the positive electrode layer; depositing a solid electrolyte precursor on the substrate over the positive electrode layer to form a solid electrolyte layer; compacting a solid electrolyte layer on the substrate above the positive electrode layer to form a composite structure; and heat treating the composite structure to sinter the solid electrolyte layer. The positive electrode precursor includes electroactive material particles, solid electrolyte particles, and conductive particles. The solid electrolyte precursor includes solid electrolyte particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to solid electrolytes for cycling lithium-ion batteries, and more particularly to methods of making a composite structure including a positive electrode and a solid electrolyte covering the positive electrode. Background Art

[0002] The information provided in this section is for the purpose of generally presenting the background of the present disclosure. The work of the presently named inventors, to the extent described in this section, and aspects of the description that may not constitute prior art at the time of filing are neither expressly nor impliedly admitted to be prior art to the present disclosure.

[0003] A battery pack for circulating lithium ions generally includes a negative electrode, a positive electrode and an electrolyte, which provides a medium for conducting lithium ions between the negative electrode and the positive electrode. The electrolyte can be in the form of a liquid, a solid or a gel. Compared with a battery pack including a liquid electrolyte, a solid-state battery pack including a solid electrolyte has a higher energy density, does not require the use of an organic solvent, is not easy to swell, and can inhibit the formation of lithium dendrites. The solid electrolyte can be formulated and manufactured to exhibit a desirable combination of features, including a relatively small thickness to achieve a fast charging rate and a high current density, high uniformity and crack-free to ensure a uniform current density distribution and prevent the formation of lithium dendrites, and the ability to establish and maintain good interfacial contact with the electrode surface to reduce the interface resistance and ensure sufficient battery pack cycle life. Summary of the invention

[0004] A method for manufacturing a composite structure for a battery pack for cycling lithium ions is disclosed. In the method, a positive electrode precursor is deposited on a substrate to form a positive electrode layer having a first end, an opposite second end, and a facing surface extending between the first end and the opposite second end. The positive electrode precursor comprises electroactive material particles, solid electrolyte particles, and conductive particles. The positive electrode layer is compacted on the substrate. Then, a solid electrolyte precursor is deposited on the substrate above the positive electrode layer to form a solid electrolyte layer having a main facing surface. The solid electrolyte precursor comprises solid electrolyte particles. The solid electrolyte layer is compacted on the substrate above the positive electrode layer to form a composite structure including the positive electrode layer and the solid electrolyte layer. The composite structure is heat treated to sinter the solid electrolyte layer.

[0005] The positive electrode precursor may be prepared by mixing the electroactive material particles, the solid electrolyte particles and the conductive particles together in an extruder. In this case, the positive electrode precursor may be deposited on the substrate via extrusion.

[0006] The method may further include applying a liquid electrolyte solution to the positive electrode layer to form a solid interphase layer on the surface of the electroactive material particles before depositing the solid electrolyte precursor on the substrate above the positive electrode layer.

[0007] The solid electrolyte precursor may be deposited on the substrate above the positive electrode layer via extrusion.

[0008] The positive electrode layer may be compacted by applying a force greater than or equal to about 100 megapascals to a facing surface of the positive electrode layer.

[0009] The solid electrolyte layer may be compacted by applying a force of less than 100 MPa to a major facing surface of the solid electrolyte layer.

[0010] Before compacting the positive electrode layer and the solid electrolyte layer, the positive electrode layer and the solid electrolyte layer may each have a porosity greater than or equal to about 50% and less than or equal to about 70%. After compacting the positive electrode layer and the solid electrolyte layer, the positive electrode layer and the solid electrolyte layer may each have a porosity greater than or equal to about 20% and less than or equal to about 45%.

[0011] The solid electrolyte precursor can be deposited on the substrate above the positive electrode layer so that the solid electrolyte layer extends to the entire facing surface of the positive electrode layer and extends along the first end and the opposite second end of the positive electrode layer so that the positive electrode layer is completely encapsulated by the solid electrolyte layer on the substrate.

[0012] After heat treating the composite structure, the thickness of the solid electrolyte layer extending to the facing surface of the positive electrode layer may be greater than or equal to about 1 micrometer and less than or equal to about 30 micrometers.

[0013] The positive electrode precursor may further include an organic solvent. In this case, after the positive electrode precursor is deposited on the substrate, the organic solvent may be removed therefrom to form the positive electrode layer.

[0014] The solid electrolyte precursor may further include an organic solvent. In this case, after the solid electrolyte precursor is deposited on the substrate above the positive electrode layer, the organic solvent may be removed therefrom to form the solid electrolyte layer.

[0015] The composite structure may be heat treated at a temperature greater than or equal to about 1000 degrees Celsius to sinter the solid electrolyte layer.

[0016] The substrate may include a release film. In this case, the method may further include, before heat-treating the composite structure, removing the composite structure from the substrate and applying the composite structure to a major surface of a positive electrode current collector.

[0017] The composite structure may be manufactured using a continuous roll-to-roll process. In this case, the substrate may comprise a web extending between a supply roll and a take-up roll.

[0018] The positive electrode layer may be compacted by passing the positive electrode layer and the substrate between a first pair of calendering rolls. The solid electrolyte layer may be compacted by passing the solid electrolyte layer and the substrate between a second pair of calendering rolls.

[0019] The positive electrode layer may have a gradient structure. In this case, the method may further include depositing a first positive electrode precursor on the substrate to form a first positive electrode layer, and then depositing a second positive electrode precursor on the substrate above the first positive electrode layer to form a second positive electrode layer above the first positive electrode layer. The first positive electrode precursor and the second positive electrode precursor may each contain electroactive material particles, solid electrolyte particles, and conductive particles. The concentration of solid electrolyte particles in the first positive electrode precursor may be greater than the concentration of solid electrolyte particles in the second positive electrode precursor, and the concentration of conductive particles in the second positive electrode precursor may be greater than the concentration of conductive particles in the first positive electrode precursor.

[0020] The electroactive material particles may include a lithium transition metal oxide.The solid electrolyte particles may include an oxide-based solid electrolyte material, a sulfide-based solid electrolyte material, or a combination thereof.

[0021] A battery pack is disclosed that includes a composite structure manufactured by the method described herein.

[0022] A method for manufacturing a composite structure for a battery pack for cycling lithium ions is disclosed. In the method, a positive electrode precursor is deposited on a substrate to form a positive electrode layer. The positive electrode precursor comprises electroactive material particles, solid electrolyte particles and conductive particles. The solid electrolyte precursor is deposited on the substrate above the positive electrode layer to form a solid electrolyte layer above the positive electrode layer. The solid electrolyte precursor comprises solid electrolyte particles. The positive electrode precursor and the solid electrolyte precursor are deposited on the substrate substantially simultaneously by extrusion. The positive electrode layer and the solid electrolyte layer are compacted on the substrate to form a composite structure including the positive electrode layer and the solid electrolyte layer. The composite structure is transferred from the substrate to a positive electrode current collector and heat treated on the positive electrode current collector to sinter the solid electrolyte layer.

[0023] The substrate may include a polymer and the positive electrode current collector may include aluminum.

[0024] The solid electrolyte precursor may be deposited on the substrate above the positive electrode layer such that the positive electrode layer is completely encapsulated by the solid electrolyte layer on the substrate.

[0025] The present invention discloses the following scheme:

[0026] Scheme 1. A method of manufacturing a composite structure for a battery pack for cycling lithium ions, the method comprising:

[0027] (a) depositing a positive electrode precursor on a substrate to form a positive electrode layer having a first end, an opposite second end, and a facing surface extending between the first end and the opposite second end, the positive electrode precursor comprising electroactive material particles, solid electrolyte particles, and conductive particles;

[0028] (b) pressing the positive electrode layer onto the substrate;

[0029] (c) depositing a solid electrolyte precursor on the substrate above the positive electrode layer to form a solid electrolyte layer having a primary facing surface, the solid electrolyte precursor comprising solid electrolyte particles;

[0030] (d) compacting the solid electrolyte layer on the substrate above the positive electrode layer to form a composite structure including the positive electrode layer and the solid electrolyte layer; and

[0031] (e) heat-treating the composite structure to sinter the solid electrolyte layer.

[0032] Option 2. A method according to Option 1, wherein the positive electrode precursor is prepared by mixing the electroactive material particles, the solid electrolyte particles and the conductive particles together in an extruder, and wherein the positive electrode precursor is deposited on the substrate via extrusion.

[0033] Scheme 3. The method according to Scheme 1, further comprising:

[0034] Prior to step (c), a liquid electrolyte solution is applied to the positive electrode layer to form a solid interfacial layer on the surface of the electroactive material particles.

[0035] Option 4. A method according to Option 1, wherein the solid electrolyte precursor is deposited on the substrate above the positive electrode layer via extrusion.

[0036] Option 5. The method according to Option 1, wherein in step (b), the positive electrode layer is compacted by applying a force greater than or equal to about 100 MPa to the facing surface of the positive electrode layer.

[0037] Option 6. The method according to Option 1, wherein in step (d), the solid electrolyte layer is compacted by applying a force of less than 100 MPa to the main facing surface of the solid electrolyte layer.

[0038] Option 7. A method according to Option 1, wherein before the positive electrode layer and the solid electrolyte layer are respectively compacted in step (b) and step (d), the positive electrode layer and the solid electrolyte layer each have a porosity greater than or equal to about 50% and less than or equal to about 70%, and wherein after the positive electrode layer and the solid electrolyte layer are respectively compacted in step (b) and step (d), the positive electrode layer and the solid electrolyte layer each have a porosity greater than or equal to about 20% and less than or equal to about 45%.

[0039] Option 8. A method according to Option 1, wherein the solid electrolyte precursor is deposited on a substrate above the positive electrode layer, so that the solid electrolyte layer extends to the entire facing surface of the positive electrode layer and extends along the first end and the opposite second end of the positive electrode layer, so that the positive electrode layer is completely encapsulated by the solid electrolyte layer on the substrate.

[0040] Option 9. The method according to Option 1, wherein after step (e), the thickness of the solid electrolyte layer extending to the facing surface of the positive electrode layer is greater than or equal to about 1 micron and less than or equal to about 30 microns.

[0041] Embodiment 10. The method according to Embodiment 1, wherein the positive electrode precursor further comprises an organic solvent, and wherein, after depositing the positive electrode precursor on the substrate, the organic solvent is removed therefrom to form the positive electrode layer.

[0042] Option 11. A method according to Option 1, wherein the solid electrolyte precursor further comprises an organic solvent, and wherein, after depositing the solid electrolyte precursor on a substrate above the positive electrode layer, the organic solvent is removed therefrom to form the solid electrolyte layer.

[0043] Option 12. The method according to Option 1, wherein in step (e) the composite structure is heat treated at a temperature greater than or equal to about 1000 degrees Celsius to sinter the solid electrolyte layer.

[0044] Embodiment 13. The method according to embodiment 1, wherein the substrate comprises a release film, and wherein the method further comprises:

[0045] Prior to step (e), the composite structure is removed from the substrate and applied to a major surface of a positive electrode current collector.

[0046] Embodiment 14. The method of embodiment 1, wherein the composite structure is manufactured using a continuous roll-to-roll process, and wherein the substrate comprises a web extending between a supply roll and a take-up roll.

[0047] Option 15. A method according to Option 14, wherein in step (b), the positive electrode layer is compacted by passing the positive electrode layer and the substrate between a first pair of calendering rollers, and wherein in step (d), the solid electrolyte layer is compacted by passing the solid electrolyte layer and the substrate between a second pair of calendering rollers.

[0048] Embodiment 16. The method according to embodiment 1, wherein the positive electrode layer has a gradient structure, and wherein the method further comprises:

[0049] depositing a first positive electrode precursor on the substrate to form a first positive electrode layer; and then

[0050] depositing a second positive electrode precursor on the substrate above the first positive electrode layer to form a second positive electrode layer above the first positive electrode layer,

[0051] wherein the first positive electrode precursor and the second positive electrode precursor each comprise electroactive material particles, solid electrolyte particles and conductive particles,

[0052] wherein the concentration of solid electrolyte particles in the first positive electrode precursor is greater than the concentration of solid electrolyte particles in the second positive electrode precursor, and

[0053] wherein a concentration of conductive particles in the second positive electrode precursor is greater than a concentration of conductive particles in the first positive electrode precursor.

[0054] Option 17. A method according to Option 1, wherein the electroactive material particles comprise a lithium transition metal oxide, and wherein the solid electrolyte particles comprise an oxide-based solid electrolyte material, a sulfide-based solid electrolyte material, or a combination thereof.

[0055] Embodiment 18. A battery pack comprising a composite structure manufactured by the method described in Embodiment 1.

[0056] Solution 19. A method of manufacturing a composite structure for a battery pack for cycling lithium ions, the method comprising:

[0057] (a) depositing a positive electrode precursor on a substrate to form a positive electrode layer, the positive electrode precursor comprising electroactive material particles, solid electrolyte particles and conductive particles;

[0058] (b) depositing the solid electrolyte precursor on the substrate above the positive electrode layer to form the solid electrolyte layer above the positive electrode layer, the solid electrolyte precursor comprising solid electrolyte particles, the positive electrode precursor and the solid electrolyte precursor being deposited on the substrate substantially simultaneously by extrusion;

[0059] (c) compacting the positive electrode layer and the solid electrolyte layer on the substrate to form a composite structure including the positive electrode layer and the solid electrolyte layer;

[0060] (d) transferring the composite structure from a substrate to a positive electrode current collector; and

[0061] (e) heat-treating the composite structure on the positive electrode current collector to sinter the solid electrolyte layer.

[0062] Option 20. The method of Option 19, wherein the solid electrolyte precursor is deposited on the substrate above the positive electrode layer so that the positive electrode layer is completely encapsulated by the solid electrolyte layer on the substrate.

[0063] Other application areas of the present disclosure will become apparent from the detailed description, claims and drawings. The detailed description and specific examples are for illustrative purposes only and are not intended to limit the scope of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] The present disclosure will be more fully understood from the detailed description and accompanying drawings, in which:

[0065] Figure 1 is a schematic perspective view of a motor vehicle powered by a battery pack including a plurality of battery modules.

[0066] Figure 2 yes Figure 1 Schematic cross-sectional view of a portion of one of the battery modules of FIG. 1 , the battery module including a plurality of electrochemical cells or batteries that circulate lithium ions.

[0067] Figure 3 is a schematic cross-sectional view of a circulating lithium ion battery including a positive electrode, a negative electrode, and a solid electrolyte between the positive and negative electrodes.

[0068] Figure 4 Is manufacturing Figure 3Schematic diagram of steps in a method of a battery stack in which a positive electrode is deposited on a substrate and compacted by applying force to its facing surface, the positive electrode comprising electroactive material particles, solid electrolyte particles and conductive particles.

[0069] Figure 5 Is manufacturing Figure 3 A schematic diagram of the steps in a method of producing a battery in which a liquid electrolyte solution is applied to Figure 4 on the positive electrode to form a solid interface layer on the surface of the electroactive material particles.

[0070] Figure 6 Is manufacturing Figure 3 Schematic diagram of the steps in a method of a battery pack, wherein a solid electrolyte is deposited on Figure 5 The positive electrode is placed on the substrate, and then the solid electrolyte is compacted to form a composite structure including the positive electrode and the solid electrolyte.

[0071] Figure 7 Is manufacturing Figure 3 A schematic diagram of the steps in the method of a battery pack, wherein Figure 6 The composite structure is applied to the major surface of the positive electrode current collector.

[0072] Figure 8 Is manufacturing Figure 3 Schematic diagram of a battery method in which continuous roll-to-roll technology is used to form a composite structure including a positive electrode and a solid electrolyte.

[0073] Among the drawings, reference numerals may be repeated to identify similar and / or identical elements. DETAILED DESCRIPTION

[0074] The method of the present disclosure can be used to form a thin, wrinkle-free and crack-free solid electrolyte for a battery pack that cycles lithium ions. In the disclosed method, a composite structure is formed by depositing a positive electrode and a solid electrolyte on a substrate, so that the solid electrolyte is deposited on the substrate and above the positive electrode. The solid electrolyte is compacted on the substrate above the positive electrode to form a composite structure. The composite structure is then heat treated to sinter the solid electrolyte. In an aspect, before the solid electrolyte is deposited on the substrate above the positive electrode, a liquid electrolyte solution can be applied to the positive electrode to form a solid interface layer thereon, which can help prevent undesirable chemical reactions between the positive electrode and the solid electrolyte during subsequent manufacturing steps.

[0075] Forming the solid electrolyte on and over the positive electrode prior to compacting and sintering the solid electrolyte can help prevent the formation of wrinkles and cracks in the solid electrolyte, which can help prevent the formation of lithium dendrites. In addition, forming the solid electrolyte on and over the positive electrode prior to compacting and sintering the solid electrolyte can eliminate manufacturing challenges related to the brittle nature of certain solid electrolyte materials that might otherwise occur if the solid electrolyte is compacted and sintered as a separate layer prior to assembly with the positive electrode in a battery pack.

[0076] Figure 1 A motor vehicle 2 is depicted that is powered by an electric motor 4 that draws power from a battery pack 6 that includes one or more battery modules 8. The battery modules 8 may be electrically coupled together in a series and / or parallel arrangement to meet the desired capacity and power requirements of the electric motor 4, and the vehicle 2 may be a fully electric vehicle and may be powered solely by the electric motor 4, or the vehicle 2 may be a hybrid electric vehicle and may be powered by both the electric motor 4 and an internal combustion engine (not shown).

[0077] like Figure 2 As shown in , each battery module 8 includes one or more electrochemical cells or batteries 10 that circulate lithium ions. In practice, the batteries 10 in the battery module 8 are often assembled as a stack of layers, including a negative electrode layer 12, a negative electrode current collector 13, a positive electrode layer 14, a positive electrode current collector 15, and a separator layer 16. Each battery 10 is defined by a negative electrode layer 12 and a positive electrode layer 14, which are separated from each other by a separator layer 16. In practice, the separator layer 16 can be permeated by an electrolyte that provides a medium for the conduction of lithium ions between the negative electrode layer 12 and the positive electrode layer 14, or the separator layer 16 itself can be configured to act as an electrolyte. The negative electrode layer 12 is disposed on the negative electrode current collector 13 and is electrically connected to the negative electrode current collector 13, while the positive electrode layer 14 is disposed on the positive electrode current collector 15 and is electrically connected to the positive electrode current collector 15. As shown in Figure 2 As shown in , for efficiency, these layers can be stacked so that some negative electrode current collectors 13 and some positive electrode current collectors 15 are double-sided and include negative electrode layers 12 or positive electrode layers 14 on both sides thereof, respectively. In this configuration, adjacent negative electrode layers 12 and positive electrode layers 14 share a single negative electrode current collector 13 or positive electrode current collector 15, respectively.

[0078] Figure 3 An electrochemical cell or battery 20 of circulating lithium ions is depicted. The battery 20 can generate an electric current during discharge that can be used to power a load device (e.g., an electric motor 4) and can be recharged by connection to a power source. Figure 1 and 2, the battery pack 20 may be used to power the electric motor 4 of the motor vehicle 2. Additionally or alternatively, the battery pack 20 may be used in other transportation applications (e.g., motorcycles, boats, tractors, buses, motorbikes, mobile homes, campers, tanks, and aircraft), and may be used to power fixed and / or portable electronic devices, components, and devices used in a variety of other industries and applications, including, by way of non-limiting example, industry, residential and commercial construction, consumer products, industrial equipment and machinery, agricultural or farm equipment, and heavy machinery.

[0079] The battery 20 includes a negative electrode 22, a positive electrode 24, and a solid electrolyte 26 at least partially disposed between the negative electrode 22 and the positive electrode 24. The negative electrode 22 is disposed on a negative electrode current collector 30, and the positive electrode 24 is disposed on a positive electrode current collector 32. The positive electrode 24 has a first end 38, an opposite second end 40, and a facing surface 42 extending between the first end 38 and the opposite second end 40 and facing the negative electrode 22.

[0080] In practice, the negative electrode current collector 30 and the positive electrode current collector 32 are electrically coupled to a power source or load 34 (e.g., a motor 4) via an external circuit 36. The negative electrode 22 and the positive electrode 24 are configured so that when the battery 20 is at least partially charged, an electrochemical potential difference is established between the negative electrode 22 and the positive electrode 24. During discharge of the battery 20, the electrochemical potential established between the negative electrode 22 and the positive electrode 24 drives spontaneous reduction and oxidation (redox) reactions within the battery 20 and releases lithium ions and electrons at the negative electrode 22. The released lithium ions travel from the negative electrode 22 through the solid electrolyte 26 to the positive electrode 24, while electrons travel from the negative electrode 22 to the positive electrode 24 via the external circuit 36, which generates an electric current. After the negative electrode 22 has been partially or completely depleted of lithium, the battery 20 may be charged by connecting the negative electrode 22 and the positive electrode 24 to a power source 34, which drives a non-spontaneous redox reaction within the battery 20 and the release of lithium ions and electrons from the positive electrode 24. The repeated discharge and charge of the battery 20 may be referred to herein as a "cycle," wherein a full charge event and a subsequent full discharge event are considered a full cycle.

[0081] The solid electrolyte 26 extends between the negative electrode 22 and the positive electrode 24 and provides a medium for conducting lithium ions between the negative electrode 22 and the positive electrode 24 through the battery 20. In addition, the solid electrolyte 26 physically separates and electrically isolates the negative electrode 22 and the positive electrode 24 from each other while allowing lithium ions to pass therethrough. Figure 3As shown, the solid electrolyte 26 can extend to the entire facing surface 42 of the positive electrode 24, and can extend from the facing surface 42 of the positive electrode 24 along the first end 38 and the opposite second end 40 of the positive electrode 24, so that the positive electrode 24 is completely encapsulated by the solid electrolyte 26. The solid electrolyte 26 can have a width defined between the negative electrode 22 and the positive electrode 24 that is greater than or equal to about 0.5 micrometers (μm), or optionally greater than or equal to about 10 μm and less than or equal to about 50 μm, or optionally less than or equal to about 30 μm.

[0082] like Figure 7 As best shown in FIG. 4 , solid electrolyte 26 includes ionically conductive solid electrolyte particles 44 and optionally one or more additives (not shown). Solid electrolyte particles 44 may have an average particle size greater than or equal to about 0.1 μm and less than or equal to about 20 μm.

[0083] The solid electrolyte particles 44 include an ion-conductive solid electrolyte material. For example, the solid electrolyte particles 44 may include an inorganic solid electrolyte material, a solid polymer electrolyte material, or a combination thereof. Examples of inorganic solid electrolyte materials include oxide-based solid electrolyte materials and sulfide-based solid electrolyte materials. Examples of oxide-based solid electrolyte materials include NASICON-type solid electrolyte materials (e.g., Li 1.4 Al 0.4 Ti 1.6 (PO4)3), LISICON type solid electrolyte materials (such as Li 2+2x Zn 1-x GeO4), perovskite solid electrolyte materials (such as Li 3x La 2 / 3-x TiO3), garnet-type solid electrolyte materials (such as Li7La3Zr2O 12 ), and / or metal-doped or alivalently substituted metal oxide-based solid electrolyte materials (e.g., Al- or Nb-doped Li7La3Zr2O 12 , Sb-doped Li7La3Zr2O 12 , Ga-substituted Li7La3Zr2O 12 , Cr and V substituted LiSn2P3O 12 , and / or Al-substituted perovskites, Li 1+x+y Al x Ti 2-x Si y P 3-y O 12.Examples of sulfide-based solid electrolyte materials include argyrodite materials represented by the formula Li6PS5X, where X = Cl, Br, I; and 9.6 P3S 12 and / or Li7P3S 11 A lithium phosphosulfide material represented by one or more of the formula Li 11-x M 2-x P 1+x S 12 LGPS type materials represented by M = Ge, Sn, Si (e.g., Li 10 GeP2S 12 、Li9P3S9O3、Li 10.35 Ge 1.35 P 1.65 S 12 , Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 , Li 10 (Ge 0.5 Sn 0.5 )P2S 12 , and / or Li 10 (Si 0.5 Sn 0.5 )P2S 12 ); Li2S-P2S5 type materials; Li2S-P2S5-MO X Type material; Li2S-P2S5–MS x Type materials; sulfide LISICON type materials (such as Li 3.25 Ge 0.25 P 0.75 S4); Li 3.4 Si 0.4 P 0.6 S4; Li 10 GeP2S 11.7 O 0.3 ;Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 ;Li 3.833 Sn 0.833 As0.166 S4; LiI-Li4SnS4; and / or Li4SnS4. Examples of solid polymer electrolyte materials include polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and combinations thereof.

[0084] The positive electrode 24 is configured to reversibly store and release lithium ions during discharge and charge of the battery 20, and is in the form of a continuous porous layer disposed on a major surface of the positive electrode current collector 32. Figure 7 As best shown in FIG. 4 , positive electrode 24 includes electrochemically active (electroactive) material particles 46 , solid electrolyte particles 44 , conductive particles 48 , and an optional polymer binder (not shown).

[0085] The electroactive material particles 46 are uniformly distributed throughout the positive electrode 24 and include an electroactive material that can store and release lithium ions by undergoing a reversible redox reaction with lithium at a higher electrochemical potential than the electroactive material of the negative electrode 22, so that there is an electrochemical potential difference between the negative electrode 22 and the positive electrode 24. For example, the electroactive material particles 46 can include a material that can undergo lithium intercalation and deintercalation or a material that can undergo a conversion reaction with lithium. In the aspect that the electroactive material particles 46 include an intercalation host material that can undergo reversible insertion or intercalation of lithium ions, the electroactive material particles 46 can include a lithium transition metal oxide. For example, the electroactive material particles 46 may include a layered lithium transition metal oxide represented by the formula LiMeO2, an olivine-type lithium transition metal oxide represented by the formula LiMePO4, a monoclinic lithium transition metal oxide represented by the formula Li3Me2(PO4)3, a spinel-type lithium transition metal oxide represented by the formula LiMe2O4, tavorite represented by one or both of the following formulas LiMeSO4F or LiMePO4F, or a combination thereof, wherein Me is a transition metal (e.g., Co, Ni, Mn, Fe, Al, V, or a combination thereof). In the aspect that the electroactive material particles 46 comprise a conversion material, the electroactive material particles 46 may comprise sulfur, selenium, tellurium, iodine, halides (e.g., fluorides or chlorides), sulfides, selenides, tellurides, iodides, phosphides, nitrides, oxides, sulfur oxides, fluorides, sulfur-fluorides, sulfur-oxyfluorides, or lithium and / or metal compounds thereof (e.g., compounds of iron, manganese, nickel, copper, and / or cobalt). The electroactive material particles 46 may constitute greater than or equal to about 50%, optionally greater than or equal to about 60%, or optionally greater than or equal to about 70% and less than or equal to about 95%, optionally less than or equal to about 90%, or optionally less than or equal to about 80% by weight of the positive electrode 24.

[0086] In one embodiment, a solid interface layer 52 may be disposed on and over the outer surface of each electroactive material particle 46. The solid interface layer 52 may include an electrically insulating and ionically conductive material and may be formulated to prevent undesirable chemical reactions between the electroactive material particles 46 in the positive electrode 24 and the solid electrolyte particles 44 in the solid electrolyte 26.

[0087] The solid interface layer 52 may include decomposition products of the liquid electrolyte solution. The optional solid interface layer 52 may be formed on the outer surface of each electroactive material particle 46 after forming the positive electrode 24 and before assembling the battery 20.

[0088] The solid electrolyte particles 44 included in the positive electrode 24 may include one or more ion-conductive solid electrolyte materials disclosed above with respect to the solid electrolyte 26. The solid electrolyte particles 44 included in the positive electrode 24 may have the same composition or a different composition as the solid electrolyte particles 44 included in the solid electrolyte 26. The solid electrolyte particles 44 may constitute greater than 0%, optionally greater than or equal to about 10%, or optionally greater than or equal to about 15% and less than or equal to about 30%, or optionally less than or equal to about 20% by weight of the positive electrode 24.

[0089] Conductive particles 48 are electrochemically inert and are included in the positive electrode 24 to provide sufficient conductivity to the positive electrode 24 to support the penetration of electrons therethrough. Conductive particles 48 comprise a conductive material. Examples of conductive materials include carbon-based materials, metals (e.g., nickel), and / or conductive polymers. Examples of conductive carbon-based materials include carbon black (CB) (e.g., acetylene black), graphite, graphene (e.g., graphene nanosheets, GNPs), graphene oxide, carbon nanotubes (CNTs), and / or carbon fibers (e.g., carbon nanofibers). Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, and / or polypyrrole. Conductive particles 48 may constitute greater than 0%, optionally greater than or equal to about 1%, or optionally greater than or equal to about 5% and less than or equal to about 10% of the positive electrode 24 by weight.

[0090] The optional polymer binder is electrochemically inert and may be included in the positive electrode 24 to provide structural integrity to the positive electrode 24 and / or to help the positive electrode 24 adhere to the major surface of the positive electrode current collector 32. Examples of polymer binders include polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), ethylene propylene diene monomer (EPDM) rubber, styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-butadiene rubber (SBR), styrene ethylene butylene styrene copolymer (SEBS), polyacrylates, alginates, polyacrylic acid, and combinations thereof. When present, the polymer binder may constitute greater than or equal to about 1%, or optionally greater than or equal to about 5%, and less than or equal to about 10% by weight of the positive electrode 24.

[0091] In an aspect, the positive electrode 24 may have a gradient structure (not shown) in which the proximal region of the positive electrode 24 is close to and extends along the main surface of the positive electrode current collector 32, and the distal region of the positive electrode 24 extends on the proximal region along the facing surface 42 of the positive electrode 24. In this case, the composition of the proximal region of the positive electrode 24 may be different from the composition of the distal region of the positive electrode 24. For example, the concentration of the solid electrolyte particles 44 in the proximal region of the positive electrode 24 may be greater than the concentration of the solid electrolyte particles 44 in the distal region of the positive electrode 24. Additionally or alternatively, the concentration of the conductive particles 48 in the distal region of the positive electrode 24 may be greater than the concentration of the conductive particles 48 in the proximal region of the positive electrode 24.

[0092] The negative electrode 22 is configured to store and release lithium ions during charging and discharging of the battery 20, and the negative electrode 22 may be in the form of a continuous material layer disposed on a major surface of the negative electrode current collector 30. The negative electrode 22 includes an electrochemically active (electroactive) material (electroactive negative electrode material) that can store and release lithium ions by undergoing a reversible redox reaction with lithium during charging and discharging of the battery 20. Examples of electroactive materials for the negative electrode 22 include lithium, lithium-based materials, lithium alloys (e.g., alloys of lithium with silicon, aluminum, indium, tin, or a combination thereof), carbon-based materials (e.g., graphite, activated carbon, carbon black, hard carbon, soft carbon, and / or graphene), silicon, silicon-based materials (e.g., silicon oxide, alloys of silicon with tin, iron, aluminum, cobalt, or a combination thereof, and / or composite materials of silicon and / or silicon oxide and carbon), tin oxide, aluminum, indium, zinc, germanium, silicon oxide, lithium silicon oxide, lithium silicide, titanium oxide, lithium titanate, and combinations thereof. The electroactive material of negative electrode 22 may constitute greater than or equal to about 50%, optionally greater than or equal to about 60%, or optionally greater than or equal to about 70% and less than or equal to about 95%, optionally less than or equal to about 90%, or optionally less than or equal to about 80% by weight of negative electrode 22.

[0093] In one aspect, the electroactive material of the negative electrode 22 may be composed of lithium, and the negative electrode 22 may be in the form of a non-porous metal film or foil, such as a lithium metal film or a lithium metal foil. In other aspects, the negative electrode 22 may be porous, and the electroactive material of the negative electrode 22 may be a granular material. In aspects where the electroactive material of the negative electrode 22 is a granular material, the particles of the electroactive material of the negative electrode 22 may be blended with particles of a solid electrolyte material, a polymer binder, and an optional conductive material. The same solid electrolyte material, polymer binder, and / or conductive material as disclosed above with respect to the positive electrode 24 may be used for the negative electrode 22 in substantially the same amount.

[0094] The negative electrode current collector 30 and the positive electrode current collector 32 are conductive and provide an external circuit 36 ​​with electrical connections between their respective negative electrode 22 and positive electrode 24. In one aspect, the negative electrode current collector 30 and the positive electrode current collector 32 can be in the form of a non-porous metal foil, a perforated metal foil, a porous metal mesh, or a combination thereof. The negative electrode current collector 30 can be made of copper, nickel or its alloy, stainless steel, or other suitable conductive materials. The positive electrode current collector 32 can be made of aluminum (Al) or another suitable conductive material.

[0095] method

[0096] Reference now Figure 4 , 5 , 6, 7 and 8, the positive electrode 24 and the solid electrolyte 26 can be manufactured by a method including one or more of the following steps. In one aspect, the method can be performed as a batch process. In other aspects, the method can be performed as a continuous roll-to-roll process, such as Figure 8 shown.

[0097] A positive electrode precursor 102 is prepared, which includes electroactive material particles 46, solid electrolyte particles 44, conductive particles 48, and an optional polymer binder in an organic solvent. The organic solvent may include a polar aprotic organic solvent, such as acetonitrile, tetrahydrofuran, or a combination thereof. In one embodiment, the positive electrode precursor 102 can be prepared by mixing the electroactive material particles 46, solid electrolyte particles 44, conductive particles 48, an optional polymer binder, and an organic solvent together in a first extruder 104, such as Figure 8 shown.

[0098] The positive electrode precursor 102 is deposited on the substrate 50 to form a positive electrode precursor layer 106. In one aspect, the substrate 50 may include a separate release film, which may include a polymer. In other aspects, the substrate 50 may include the positive electrode current collector 32, or may be made of the same material as the positive electrode current collector 32 and have the same thickness as the positive electrode current collector 32. In any embodiment, the substrate 50 may be in the form of a continuous web extending between a supply roll 108 and a take-up roll 110. As shown in FIG. Figure 8 In the illustrated aspect, the positive electrode precursor 102 may be deposited on the substrate 50 by extrusion from a first extruder 104 .

[0099] After the positive electrode precursor layer 106 is deposited on the substrate 50, the organic solvent is removed therefrom (e.g., by evaporation) to form the positive electrode 24 on the substrate 50, such as Figure 4 and Figure 8 By heating the positive electrode precursor layer 106 at a temperature of less than or equal to about 200° C., or optionally less than or equal to about 100° C., the organic solvent can be removed from the positive electrode precursor layer 106. Figure 8 In the illustrated aspect, the organic solvent may be removed from the positive electrode precursor layer 106 by passing the positive electrode precursor layer 106 through a heater 112 .

[0100] In the aspect that the positive electrode 24 has a gradient structure, the positive electrode 24 may be formed by preparing a first positive electrode precursor and a second positive electrode precursor (not shown). The concentration of the solid electrolyte particles 44 in the first positive electrode precursor may be greater than the concentration of the solid electrolyte particles 44 in the second positive electrode precursor, and the concentration of the conductive particles 48 in the second positive electrode precursor may be greater than the concentration of the conductive particles 48 in the first positive electrode precursor. The first positive electrode precursor may be deposited on a substrate 50 to form a first positive electrode layer, and then the second positive electrode precursor may be deposited on the substrate 50 above the first positive electrode layer to form a second positive electrode layer above the first positive electrode layer.

[0101] The positive electrode 24 is compacted on the substrate 50 to reduce its porosity. Figure 4 As shown, the positive electrode 24 can be compacted by applying a force 54 to the facing surface 42 of the positive electrode 24. The force 54 applied to the facing surface 42 of the positive electrode 24 can be greater than or equal to about 100 megapascals (Mpa). The positive electrode 24 can be compacted at a temperature of less than or equal to about 200°C, or optionally less than or equal to about 100°C. In aspects, the positive electrode 24 can be compacted at ambient temperature (e.g., 25°C). In aspects, the force 54 can be applied to the facing surface 42 of the positive electrode 24 using a uniaxial pressing technique. In other aspects, the force 54 can be applied to the facing surface 42 of the positive electrode 24 using a calendering method, wherein the positive electrode 24 passes between a pair of calendering rollers 114, such as Figure 8 Before compacting the positive electrode 24, the positive electrode 24 may have a porosity of greater than or equal to about 50% and less than or equal to about 70%. After compacting the positive electrode 24, the positive electrode 24 may have a porosity of greater than or equal to about 20% and less than or equal to about 45%.

[0102] like Figure 5 and Figure 8As shown, in the aspect, a liquid electrolyte solution 56 can be applied to the positive electrode 24 to form a solid interface layer 52 on and above the outer surface of the electroactive material particles 46. The liquid electrolyte solution 56 may include a lithium fluoride salt dissolved in an organic solvent and / or an ionic liquid. Examples of lithium fluoride salts include lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2), lithium bis(fluorosulfonyl)imide (LiN(FSO2)2)(LiSFI), lithium difluoro(oxalato)borate (LiBF2(C2O4))(LiDFOB), and combinations thereof. The organic solvent may include a non-aqueous aprotic organic solvent. Non-limiting examples of non-aqueous aprotic organic solvents include cyclic carbonates (e.g., ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC), and vinylene carbonate (VC)); linear carbonates (e.g., dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC)); aliphatic carboxylates (e.g., methyl formate, methyl acetate, methyl propionate); lactones (e.g., γ-butyrolactone, γ-valerolactone, and / or δ-valerolactone); nitriles (e.g., succinonitrile, valerolactone, and / or valerolactone); dinitriles and / or adiponitrile); sulfones (e.g., tetramethylene sulfone, ethyl methyl sulfone, vinyl sulfone, phenyl sulfone, 4-fluorophenyl sulfone, benzyl sulfone and / or cyclopentane sulfone); aliphatic ethers (e.g., triethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, 1,3-dimethoxypropane, 1,2-dimethoxyethane, 1,2-diethoxyethane and / or ethoxymethoxyethane); cyclic ethers (e.g., 1,4-dioxane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane); phosphates (e.g., triethyl phosphate and / or trimethyl phosphate); and combinations thereof.

[0103] An electrolyte precursor 116 is prepared, which includes solid electrolyte particles 44 and optional additives in an organic solvent. The organic solvent used to prepare the electrolyte precursor may include a polar aprotic organic solvent, such as acetonitrile, tetrahydrofuran, or a combination thereof. The electrolyte precursor 116 is deposited on the substrate 50 above the positive electrode 24 to form an electrolyte precursor layer 118. In one embodiment, the electrolyte precursor 116 can be prepared by mixing the solid electrolyte particles 44, the optional additives, and the organic solvent together in a second extruder 120, and then extruding the electrolyte precursor 116 on the substrate 50 above the positive electrode 24, such as Figure 8 shown.

[0104] The electrolyte precursor 116 can be deposited on the substrate 50 such that the electrolyte precursor layer 118 extends from the first end 38 of the positive electrode 24 to the opposite second end 40 of the positive electrode 24 over the entire facing surface 42 of the positive electrode 24. In addition, the electrolyte precursor layer 118 can extend from the facing surface 42 of the positive electrode 24 along the first end 38 of the positive electrode 24 and along the opposite second end 40 of the positive electrode 24. In other words, the electrolyte precursor 116 can be deposited on the substrate 50 above the positive electrode 24 such that the positive electrode 24 is completely encapsulated by the electrolyte precursor layer 118.

[0105] The organic solvent is then removed from the electrolyte precursor layer 118 (eg, by evaporation) to form a solid electrolyte 26 on the substrate 50 above the positive electrode 24, as shown in FIG. Figure 6 and Figure 8 The organic solvent can be removed from the electrolyte precursor layer 118 by heating the electrolyte precursor layer 118 at a temperature of less than or equal to about 200° C., or optionally less than or equal to about 100° C. Figure 8 As shown, in some aspects, the organic solvent can be removed from the electrolyte precursor layer 118 by passing the electrolyte precursor layer 118 through the heater 122. As with the electrolyte precursor 116, the solid electrolyte 26 can extend from the first end 38 of the positive electrode 24 to the opposite second end 40 across the entire facing surface 42 of the positive electrode 24. In addition, the solid electrolyte 26 can extend from the facing surface 42 of the positive electrode 24 along the first end 38 of the positive electrode 24 and along the opposite second end 40 of the positive electrode 24, such that the positive electrode 24 is completely encapsulated by the solid electrolyte 26.

[0106] For example, by applying force 58 to facing surface 60 of solid electrolyte 26, solid electrolyte 26 is compacted onto substrate 50 above positive electrode 24 to reduce its porosity, such as Figure 6 As shown. The solid electrolyte 26 may be compacted at a temperature of about 100° C. or greater, or optionally about 200° C. or greater. The force 58 applied to the facing surface 60 of the solid electrolyte 26 may be less than about 100 megapascals (MPa). In one aspect, the force 58 may be applied to the facing surface 60 of the solid electrolyte 26 using a uniaxial pressing technique. In other aspects, the force 58 may be applied to the facing surface 60 of the solid electrolyte 26 using a calendering method, wherein the solid electrolyte 26 passes between a pair of calendering rollers 124, such as Figure 8 Before compacting the solid electrolyte 26, the solid electrolyte 26 may have a porosity of greater than or equal to about 50% and less than or equal to about 70%. After compacting the solid electrolyte 26, the solid electrolyte 26 may have a porosity of greater than or equal to about 20% and less than or equal to about 45%.

[0107] The compacted positive electrode 24 and the compacted solid electrolyte 26 together define a composite structure 62 .

[0108] In embodiments where substrate 50 includes a release film, after forming composite structure 62, composite structure 62 including positive electrode 24 and solid electrolyte 26 can be removed from substrate 50 and applied to a major surface of positive electrode current collector 32, such as Figure 7 The composite structure 62 may be applied to the major surface of the positive electrode current collector 32, for example, by lamination.

[0109] The composite structure 62 may be heat treated to sinter the positive electrode 24 and / or the solid electrolyte 26. In one embodiment, the composite structure 62 may be heat treated by passing the composite structure 62 through a heater 126, such as Figure 8 In an aspect, the composite structure 62 can be heat treated while the composite structure 62 is disposed on the major surface of the positive electrode current collector 32. The composite structure 62 can be heat treated, for example, by heating the composite structure 62 at a temperature greater than or equal to about 400 degrees Celsius (°C), optionally greater than or equal to about 500°C, optionally greater than or equal to about 800°C, optionally greater than or equal to about 1000°C, optionally greater than or equal to about 1200°C, or optionally greater than or equal to about 1500°C.

[0110] Without intending to be bound by theory, it is believed that forming the solid electrolyte 26 on and over the positive electrode 24 prior to heat treating the solid electrolyte 26 may allow for the formation of a solid electrolyte 26 that is free of wrinkles and cracks, which may help prevent the formation of lithium dendrites that may otherwise form on the negative electrode 22 and penetrate into the solid electrolyte 26 during cycling of the battery 20. Additionally, it is believed that forming the solid electrolyte 26 on and over the positive electrode 24 prior to heat treating the solid electrolyte 26 may allow for the formation of a relatively thin solid electrolyte 26 as compared to a separate solid electrolyte layer formed and heat treated prior to application to the negative or positive electrode surface.

[0111] After heat treating the composite structure 62 , the composite structure 62 and the positive electrode current collector 32 may be assembled into the battery pack 20 .

[0112] In aspects where the composite structure 62 is manufactured using a continuous roll-to-roll process, after the composite structure 62 is heat treated, the composite structure 62 and the substrate 50 may be wound onto a take-up roll 110, such as Figure 8 Thereafter, portions of the composite structure 62 may be cut from the take-up roll and assembled into the battery pack 20 .

[0113] The foregoing description is merely illustrative and is by no means intended to limit the present disclosure, its application or use. The broad teachings of the present disclosure can be implemented in various forms. Therefore, although the present disclosure includes specific examples, the true scope of the present disclosure should not be so limited, because after studying the drawings, the specification and the appended claims, other modifications will become apparent. It should be understood that, without changing the principles of the present disclosure, one or more steps in the method can be performed in different orders (or simultaneously). In addition, although each embodiment is described above as having certain features, any one or more of those features described in any embodiment of the present disclosure can be implemented in any other embodiment and / or combined with the features of any other embodiment, even if the combination is not explicitly described. In other words, the embodiments described are not mutually exclusive, and the replacement of one or more embodiments with each other remains within the scope of the present disclosure.

[0114] The terms used herein are only for the purpose of describing the exemplary embodiments and are not intended to be limiting. As used herein, the singular forms "a", "an", and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise. The terms "comprises", "comprising", "including", and "having" are inclusive, thus specifying the presence of the features, elements, compositions, steps, integers, operations, and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts, and / or groups thereof. Although the open-ended terms "comprises", "comprising", "including", and "having" should be understood as non-limiting terms for describing and claiming the various embodiments described herein, in some aspects, the terms may alternatively be understood as more restrictive and constraining terms, such as "consisting of" or "consisting essentially of". Thus, for any given embodiment reciting compositions, materials, parts, elements, ingredients, features, integers, operations, and / or process steps, the present disclosure also specifically includes embodiments consisting of or consisting essentially of such described compositions, materials, parts, elements, ingredients, features, integers, operations, and / or process steps. In the case of "consisting of," alternative embodiments exclude any additional compositions, materials, parts, elements, ingredients, features, integers, operations, and / or process steps, while in the case of "consisting essentially of," any additional compositions, materials, parts, elements, ingredients, features, integers, operations, and / or process steps that materially affect the basic and novel characteristics are excluded from such embodiments, but any compositions, materials, parts, elements, ingredients, features, integers, operations, and / or process steps that do not materially affect the basic and novel characteristics may be included in such embodiments.

[0115] Any method steps, processes, and operations described herein should not be construed as necessarily requiring their execution in the order discussed or illustrated, unless specifically identified as an order of execution. It should also be understood that additional or alternative steps may be employed unless otherwise specified.

[0116] Although the terms first, second, third, etc. may be used in this article to describe various steps, elements, components, regions, layers and / or sections, these steps, elements, components, regions, layers and / or sections should not be limited by these terms unless otherwise specified. These terms can only be used to distinguish a step, element, component, region, layer or section from another step, element, component, region, layer or section. Terms such as "first", "second" and other ordinal terms do not imply order or sequence when used in this article, unless the context clearly indicates. Therefore, the first step, element, component, region, layer or section discussed below can be referred to as the second step, element, component, region, layer or section without departing from the teaching of the exemplary embodiment.

[0117] Throughout this disclosure, numerical values ​​represent approximate measures or limits of ranges and include minor deviations from given values ​​and embodiments having approximately the values ​​mentioned as well as embodiments having exactly the values ​​mentioned. Except for the working examples provided at the end of the specific embodiments, all numerical values ​​of parameters (such as amounts or conditions) in this specification should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. The numerical values ​​of the parameters in the attached claims should be understood to be modified by the term "about" only when such term "about" appears before the numerical value. "Approximately" indicates that the numerical value allows some slight imprecision (somewhat close to exact in the value; approximately or quite close to the value; almost). If the imprecision provided by "approximately" is not understood to have such ordinary meaning in the art, the "approximately" used herein at least indicates the changes that may be caused by the ordinary methods of measuring and using such parameters. For example, "about" may include less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in certain aspects, optionally less than or equal to 0.1%. In addition, the disclosure of ranges includes the disclosure of all values ​​and the disclosure of further divided ranges within the entire range, including the endpoints and subranges given for the ranges.

[0118] As used herein, the terms "composition" and "material" are used interchangeably to refer generally to a substance containing at least a preferred chemical constituent, element, or compound, but which may also contain additional elements, compounds, or substances, including trace amounts of impurities, unless otherwise specified. An "X-based" composition or material generally refers to a composition or material in which "X" is the single largest component based on a weight percentage (%). This can include compositions or materials having greater than 50% X by weight, as well as those having less than 50% X by weight, as long as X is the single largest component of the composition or material based on its total weight. When a composition or material is referred to as being "substantially free" of a substance, the composition or material may contain less than 5%, optionally less than 3%, optionally less than 1%, or optionally less than 0.1% of the substance by weight.

[0119] As used herein, the term "metal" may refer to a pure elemental metal, or to an alloy of an elemental metal and one or more other metals or nonmetallic elements, referred to as "alloying" elements. Alloying elements may be selected to impart desirable properties to the alloy that are not possessed by certain base metal elements.

Claims

1. A method of manufacturing a composite structure for a battery pack for cycling lithium ions, the method comprising: (a) depositing a positive electrode precursor on a substrate to form a positive electrode layer having a first end, an opposite second end, and a facing surface extending between the first end and the opposite second end, the positive electrode precursor comprising electroactive material particles, solid electrolyte particles, and conductive particles, the electroactive material particles comprising a lithium transition metal oxide; (b) pressing the positive electrode layer onto the substrate; (c) depositing a solid electrolyte precursor on the substrate above the positive electrode layer to form a solid electrolyte layer having a primary facing surface, the solid electrolyte precursor comprising solid electrolyte particles comprising an oxide-based solid electrolyte material, a sulfide-based solid electrolyte material, or a combination thereof; (d) compacting the solid electrolyte layer on the substrate above the positive electrode layer to form a composite structure including the positive electrode layer and the solid electrolyte layer; and (e) heat-treating the composite structure to sinter the solid electrolyte layer.

2. The method of claim 1, further comprising: Prior to step (c), a liquid electrolyte solution is applied to the positive electrode layer to form a solid interfacial layer on the surface of the electroactive material particles.

3. The method of claim 1, wherein the positive electrode precursor is prepared by mixing the electroactive material particles, the solid electrolyte particles and the conductive particles together in an extruder, wherein the positive electrode precursor is deposited on the substrate via extrusion, and wherein the solid electrolyte precursor is deposited on the substrate above the positive electrode layer via extrusion.

4. The method of claim 1, wherein in step (b), the positive electrode layer is compacted by applying a force greater than or equal to about 100 MPa to the facing surface of the positive electrode layer, wherein in step (d), the solid electrolyte layer is compacted by applying a force less than 100 MPa to the main facing surface of the solid electrolyte layer, wherein before the positive electrode layer and the solid electrolyte layer are compacted in steps (b) and (d), respectively, the positive electrode layer and the solid electrolyte layer each have a porosity greater than or equal to about 50% and less than or equal to about 70%, and wherein after the positive electrode layer and the solid electrolyte layer are compacted in steps (b) and (d), respectively, the positive electrode layer and the solid electrolyte layer each have a porosity greater than or equal to about 20% and less than or equal to about 45%.

5. The method of claim 1, wherein the solid electrolyte precursor is deposited on the substrate above the positive electrode layer so that the solid electrolyte layer extends to the entire facing surface of the positive electrode layer and extends along the first end and the opposite second end of the positive electrode layer so that the positive electrode layer is completely encapsulated by the solid electrolyte layer on the substrate, and wherein after step (e), the thickness of the solid electrolyte layer extending to the facing surface of the positive electrode layer is greater than or equal to about 1 micron and less than or equal to about 30 microns.

6. The method of claim 1, wherein the positive electrode precursor further comprises an organic solvent, wherein After the positive electrode precursor is deposited on the substrate, the organic solvent is removed therefrom to form the positive electrode layer, wherein the solid electrolyte precursor further comprises an organic solvent, and wherein, after the solid electrolyte precursor is deposited on the substrate above the positive electrode layer, the organic solvent is removed therefrom to form the solid electrolyte layer.

7. The method of claim 1, wherein in step (e) the composite structure is heat treated at a temperature greater than or equal to about 1000 degrees Celsius to sinter the solid electrolyte layer.

8. The method of claim 1, wherein the substrate comprises a release film, and wherein the method further comprises: Prior to step (e), the composite structure is removed from the substrate and applied to a major surface of a positive electrode current collector.

9. The method of claim 1, wherein the composite structure is manufactured using a continuous roll-to-roll process, and wherein the substrate comprises a web extending between a supply roll and a take-up roll.

10. The method of claim 1, wherein the positive electrode layer has a gradient structure, and wherein the method further comprises: depositing a first positive electrode precursor on the substrate to form a first positive electrode layer; Then depositing a second positive electrode precursor on the substrate above the first positive electrode layer to form a second positive electrode layer above the first positive electrode layer, wherein the first positive electrode precursor and the second positive electrode precursor each comprise electroactive material particles, solid electrolyte particles and conductive particles, wherein the concentration of solid electrolyte particles in the first positive electrode precursor is greater than the concentration of solid electrolyte particles in the second positive electrode precursor, and wherein a concentration of conductive particles in the second positive electrode precursor is greater than a concentration of conductive particles in the first positive electrode precursor.